First, Second, Native, Foreign, Heritage, Dominant, and Mother Tongue: Clear or Confusing? - Pelila, John Rey Osben (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Identifying and naming the languages people use is more complicated than it may seem. The terms used to describe them, such as first language (L1), mother tongue (MT), native language (NL), second language (L2), foreign language (FL), heritage language (HL), and dominant language (DL), are often applied in overlapping or inconsistent ways. As a result, confusion can arise in research, classrooms, and policy discussions. To address this issue, 22 peer-reviewed articles published in 2025 that defined or compared these terms were reviewed. The findings show that each term has a distinct focus. For example, L1 refers to the order of acquisition. In addition, MT and HL emphasize culture and family ties. Moreover, L2 and FL differ in terms of everyday use. Finally, DL reflects social power and institutions. Clarifying these differences is important for improving research accuracy and helping schools and policies respect multilingual learners. Despite these insights, the study has limitations. It relied mainly on how terms are defined in literature and did not examine how teachers, students, and policymakers understand them in practice. Another limitation is that language practices such as translanguaging and code-switching often blur the boundaries between languages, making it difficult to place them into strict categories. For this reason, future research should examine how these practices intersect with language-related terms and to what extent they expose the limits of such labels in capturing real multilingual experiences.